2018
DOI: 10.1007/978-3-030-02053-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Early Validation of User Needs in Concept Development: A Case Study in an Innovation-Oriented Consultancy

Abstract: An innovation consultancy applies human-centered methods to explore user needs in the early phase of concept development. This paper compares methods applied by the consultancy with theory from the body of knowledge within Design Thinking and Systems Engineering. The basis for this research is observations and interviews for three specific cases for three different customers. This paper presents criteria and impacting factors on how effective the innovation consultancy performs early validation of user needs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…They claimed that participatory design will enable a better exploration, user-and context understanding in this fuzzy phase. Kjørstad, Falk, Muller, and Pinto [42] proposed the use of co-creation sessions for early validation of user needs in the concept phase. Co-creation sessions are carefully planned sessions for concept exploration with customers and third parties, using tools and techniques inspired by design thinking, systems architecting, and business management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They claimed that participatory design will enable a better exploration, user-and context understanding in this fuzzy phase. Kjørstad, Falk, Muller, and Pinto [42] proposed the use of co-creation sessions for early validation of user needs in the concept phase. Co-creation sessions are carefully planned sessions for concept exploration with customers and third parties, using tools and techniques inspired by design thinking, systems architecting, and business management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In parallel with the early interviews with company representatives, we performed a literature review on design thinking and systems engineering as part of early case studies within the industry partners [42]. Thereafter we synthesized the knowledge gained from the literature and interviews, and derived success criteria to evaluate the toolbox.…”
Section: Identifying Industry Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Design thinking was defined and theorized by Rowe, Cross, Schöhn, Nelson & Stolterman (Cross, 2006;Cross, Dorst, & Roozenburg, 1992;Nelson & Stolterman, 2012;Rowe, 1987;Schön, 1982). Through its migration to management and business supported by IDEO (Brown & Katz, 2009) and described by for example Boland and Collopy (Boland & Collopy, 2004) the term has grown into a popular concept in which any business and organization could benefit to work inspired by the designer's thinking and ways of working (Tschimmel, 2012 Kjørstad, Falk, Muller, & Pinto (2019). The literature indicated that traditional systems engineering processes do not highlight the importance of focusing on user needs early in the development stages but focus on business or technology perspectives.…”
Section: State Of the Artmentioning
confidence: 99%
“…The key driver graph in Fig. 6 is based on the interviews, feedback surveys, observations, and the key driver graph by Kjørstad et al (2019). The graph in Fig.…”
Section: Figmentioning
confidence: 99%